2011
DOI: 10.5194/amt-4-47-2011
|View full text |Cite
|
Sign up to set email alerts
|

Camtracker: a new camera controlled high precision solar tracker system for FTIR-spectrometers

Abstract: Abstract.A new system to very precisely couple radiation of a moving source into a Fourier Transform Infrared (FTIR) Spectrometer is presented. The Camtracker consists of a homemade altazimuthal solar tracker, a digital camera and a homemade program to process the camera data and to control the motion of the tracker. The key idea is to evaluate the image of the radiation source on the entrance field stop of the spectrometer. We prove that the system reaches tracking accuracies of about 10 arc s for a ground-ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 22 publications
2
128
0
3
Order By: Relevance
“…There, humidity is much more variable and the moisture pathways can be best investigated by analysing the distribution of the {H 2 O,δD} pairs (e.g. Galewsky et al, 2005;Noone, 2012;González et al, 2016). Recently, there have been a variety of publications that use remote sensing observations of tropospheric {H 2 O,δD} pairs for tropospheric moisture pathway studies: for instance, for estimating the importance of rain recycling (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There, humidity is much more variable and the moisture pathways can be best investigated by analysing the distribution of the {H 2 O,δD} pairs (e.g. Galewsky et al, 2005;Noone, 2012;González et al, 2016). Recently, there have been a variety of publications that use remote sensing observations of tropospheric {H 2 O,δD} pairs for tropospheric moisture pathway studies: for instance, for estimating the importance of rain recycling (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An overall loop rate of 15-20 Hz is realized. Camera-based feedback loops without access to the Euler coordinates have previously been used to precisely track the sun from a stationary setup (Gisi et al, 2011) and a research vessel (Bertleff, 2014).…”
Section: Mobile Solar Trackermentioning
confidence: 99%
“…However, the angular diameter of the solar disk is 0.53 • in the sky, and the motion compensation system by itself is not good enough to track the sun accurately while moving. The imaging setup is needed for very high tracking precision and has previously been described in a ground-based stationary system (Gisi et al, 2011) and a research vessel (Bertleff, 2014). However, we have found that with the uneven motion on the road, the imaging setup alone cannot track the sun continuously during drives at any reasonable angular precision and duty cycle.…”
Section: Advantages Of Integrated Motion Compensation System and Imagmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the determination of pointing accuracy is a common challenge for most types of Sun-pointing instruments, and various approaches have been presented to address this issue. For example, innovative camera-based (e.g., Gisi et al, 2011) and camera-free (e.g., Reichert et al, 2015) approaches to monitor tracking accuracy have been presented in the field of solar Fourier transform infrared (FTIR) spectrometry. While Gisi et al (2011) documents a camera setup with real-time image-evaluation and tracking software (CamTrack), Reichert et al (2015) presents an approach based on subsequent FTIR measurements with a different orientation of the solar rotation axis relative to the zenith direction, which allows us to obtain both mispointing components, the component in the zenith direction, and the component perpendicular to the solar rotation axis.…”
Section: Introductionmentioning
confidence: 99%